Goethe és Schiller találkozása a filozófiában - Arató, Réka (Kultúratudományi Szemle, 2024)
The meeting of Goethe and Schiller in philosophy Despite the fact that Plato did not consider poets to be explorers of truth, we find many examples of writers and poets being interested in philosophy and discussing questions of truth or morality in their literary works or studies. Likewise we know philosophers who have reflected on the truth manifested in art or literature, such as Friedrich Nietzsche, Richard Rorty or Donald Davidson. The legendary literary and philosophical friendship between Goethe and Schiller is well known in the history of literature, and their decisive intellectual relationship lasting eleven years. Their example clearly shows the influence of literature and philosophy on each other, their debate with each other, the tension or even harmony between them.